Deep ocean particle flux in the Northeast Atlantic over the past 30 years: carbon sequestration is controlled by ecosystem structure in the upper ocean - Lampitt, R. S.; Briggs, N.; Cael, B. B.; Espinola, B.; Hélaouët, P.; Henson, S. A.; Norrbin, F.; Pebody, C. A.; Smeed, D. (Frontiers in Earth Science, 2023)
The time series of downward particle flux at 3000m at the Porcupine Abyssal Plain Sustained Observatory (PAP-SO) in the Northeast Atlantic is presented for the period 1989 to 2018. This flux can be considered to be sequestered for more than 100 years. Measured levels of organic carbon sequestration (average 1.88 g m -2 y -1 ) are higher on average at this location than at the six other time series locations in the Atlantic. Interannual variability is also greater than at the other locations (organic carbon flux coefficient of variation = 73%). We find that previously hypothesised drivers of 3000 m flux, such as upper ocean chlorophyll concentration, net primary production (NPP) and previous-winter mixing are not good predictors of this sequestration flux. In contrast, the composition of the upper ocean biological community, specifically the protozoan Rhizaria (including the Foraminifera and Radiolaria) exhibit a close relationship to sequestration flux. These species become particularly abundant following enhanced upper ocean temperatures in June leading to pulses of this material reaching 3000m depth in the late summer. In some years, the organic carbon flux pulses following Rhizaria blooms were responsible for substantial increases in carbon sequestration and we propose that the Rhizaria are one of the major vehicles by which material is transported over a very large depth range (3000m) and hence sequestered for climatically relevant time periods. We propose that they sink fast and are degraded little during their transport to depth. In terms of atmospheric CO2 uptake by the oceans, the Radiolaria and Phaeodaria are likely to have the greatest influence. Foraminifera will also exert an influence in spite of the fact that the generation of their calcite tests enhances upper ocean CO2 concentration and hence reduces uptake from the atmosphere.